PENGARUH KEJELASAN SASARAN ANGGARAN, STRUKTUR DESENTRALISASI DAN LOCUS OF CONTROL TERHADAP KINERJA MANAJERIAL - Taufik Hidayat (Akuntabilitas, 2015)
The objective of this research is to know the empirical influence of budget goalclarity, structure of decentralization, and Locus of control toward managerial performance.The data were collected by survey method are using questionaire as primer data agregation.The sample of this research are 65 leader and staff in state islamic university sharifhidayatullah Jakarta. Field research are using purposive sampling method. Data has beenanalyze use validity test, reliability test, multiple linear regression, classical assumption test,t-test, F-test and determination coefficient. The result of this research are budget goal clarityinfluence significantly to managerial performance structure of decentralization influencesignificantly to managerial performance and Locus of control not influence to managerialperformanceDOI: 10.15408/akt.v8i2.2769